Adaptação dissipativa quântica em um sistema com dois fótons - Ganascini, Thiago (2023)
Inspired by characteristics of living beings such as replication and self-organization, the dissipative adaptation theory proposed by J. England (2015) describes the probability of self-organization of classical systems out of equilibrium as a function of a source of external work. In this work, we use a completely quantum formalism, as described by D. Valente et al. (2021) in their article entitled Quantum Adaptive Dissipation, where we generalize the results obtained for the self-organization of a quantum particle system using now two uncorrelated pulses as a work source. The process is described by a model where atoms of three energy levels are directed by two pulses of single photons that, when doing work on the system, make the particle system that is initially disordered, or mixed, self-organize in a pure state irreversibly. We show that the dependence of the self-organization of the particle system follows a linearity with the work absorbed during the whole process. We also demonstrate that the absorption of the second pulse is always satisfactory in the process of self-organization of particles. We also compare the efficiency of the process for a long pulse with the use of two subsequent short pulses and demonstrate that the gain in self-organization using the two pulses is even more expressive in the case where the emission rates for each state are different.